1998
DOI: 10.1074/jbc.273.10.5829
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Mapping of the Binding Site of TrkA for Nerve Growth Factor and TrkC for Neurotrophin-3 on the Second Immunoglobulin-like Domain of the Trk Receptors

Abstract: The neurotrophins form a highly homologous family of growth factors responsible for differentiation, survival, and function of neurons sensitive to their presence (reviewed in Ref.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 61 publications
2
60
1
Order By: Relevance
“…The activation caused by deletion of the first Ig-like domain was weak in all the assays compared to that caused by deleting the second domain. The second Ig-like domain appears to be more critical in preventing spontaneous receptor dimerization, and this correlates with the more important role played by this domain in NGF binding (24,33,34,36). In platelet-derived growth factor receptors, Ig-like domains 1 to 3 participate in ligand binding; however, only deletion of the Ig-like domain 3 caused oncogenic activation (32).…”
Section: Discussionmentioning
confidence: 99%
“…The activation caused by deletion of the first Ig-like domain was weak in all the assays compared to that caused by deleting the second domain. The second Ig-like domain appears to be more critical in preventing spontaneous receptor dimerization, and this correlates with the more important role played by this domain in NGF binding (24,33,34,36). In platelet-derived growth factor receptors, Ig-like domains 1 to 3 participate in ligand binding; however, only deletion of the Ig-like domain 3 caused oncogenic activation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although the sequences of the three Trk receptors are highly similar in their intracellular domains, substantial differences in their extracellular domains (including leucine-rich regions and Ig-like regions) have been shown to contribute to NT binding specificity (Urfer et al, 1995;Windisch et al, 1995a,b;Holden et al, 1997;Ninkina et al, 1997). One recent study identified regions in and around the second Ig-like domain that were particularly important to TrkA and TrkC specificity (Urfer et al, 1998). NGF is proposed to have interactions with TrkA that are unfavorable with NT-3, based on differences in binding affinity observed with TrkA and TrkC mutants.…”
Section: Discussionmentioning
confidence: 99%
“…They are tyrosine kinases with an extracellular ligand-binding domain containing multiple repeats of leucine-rich motifs (LRR1-3), two cysteine clusters (C1, C2), two immunoglobulin-like domains (Ig1, Ig2), and a single transmembrane domain (Schneider and Schweiger 1991). Binding specificity of the Trk receptors is mostly determined by the second Ig-like domain, whereby each Trk receptor binds the corresponding ligand through a distinct specific sequence (Urfer et al 1995(Urfer et al , 1998. NGF has been crystallized in complex with the Ig2 domain of the TrkA receptor, revealing a ligand-receptor interface of two patches, where one seems to be a conserved binding motif for all family members, the other specific for the interaction between NGF and TrkA (Wiesmann et al 1999).…”
Section: Neurotrophin Signaling Uses a Two-receptor Systemmentioning
confidence: 99%